Role of Kinesiotherapy in the Prevention of Heterotopic Ossification: A Systematic Review. (28th April 2022) - Vasileiadis, George I.; Balta, Apostolia A.; Zerva, Aikaterini; Kontogiannopoulos, Vasileios; Varvarousis, Dimitrios N.; Dimakopoulos, Georgios; Ploumis, Avraam
Abstract : Objective: The role of kinesiotherapy in heterotopic ossification remains unclear. The goal of this study was to revisit the literature on the preventive role of kinesiotherapy against heterotopic ossification formation and maturation. Design: A systematic review was performed in MEDLINE, OVID, Scopus, and Cochrane databases. Results: A high-quality clinical trial is missing from the literature. Of 9617 studies primarily identified, nine studies offered the proper data and were included. They infer that satisfactory results on neurogenic heterotopic ossification prevention were achieved with passive exercises, including continuous passive motion, that were initiated early and at a painless range of motion. On the contrary, for elbow posttraumatic heterotopic ossification and major joints burn-associated heterotopic ossification, active range of motion is indicated as early as possible. Conclusions: Because of the very low quality of the studies included in this review, firm conclusions cannot be drawn about the effectiveness of kinesiotherapy. Nevertheless, it is recommended that controlled passive range of motion exercises (especially continuous passive motion) be applied early and pain-free especially in the neurogenic heterotopic ossification patients while active range of motion in painless limits is beneficial in the heterotopic ossification prevention of traumatic elbows or burn joints.